Inflammatory Fibroid Polyp: An Unusual Cause of Ileoileal Intussusception - Haley S. Adams; Brian Bergstrom; Bret Haines; Nathan Roberts (Case Reports in Surgery)
Inflammatory fibroid polyp (IFP), or Vanek’s tumor, is a rare benign lesion of the gastrointestinal tract. Clinical manifestations of IFP vary based on size and location within the GI tract. This case describes a patient who presented with hematochezia and abdominal pain. Computed tomography revealed ileoileal intussusception without a clear lead point. The patient underwent resection of the intussuscepted small bowel with primary anastomosis. A large polypoid mass was identified as the pathological lead point. Histopathological and immunohistochemical analysis revealed an IFP. Review of the literature indicates that early surgical intervention is the treatment of choice for intussusception caused by IFP. Lesions are typically reported as solitary, and resection is curative.